System verification : proving the design solution satisfies the requirements - Grady, Jeffrey O. (Academic Press, 2007)
Systems Engineering--an interdisciplinary, multi-stage-driven approach to the design and implementation of any large-scale or complex engineered product or service--has found its way from aerospace into general manufacturing as well as the services industry. It has been found to be particularly useful in such applications as software engineering, the bio- and medical industries, and large, multi-component projects like those found in energy-generation. Following on the author's previous book System Requirements Analysis, this new book will lay out the steps and procedures needed to implement.